Domestic science in negro schools - Poston, Adeline (My University, 1907)
Introduction: The terms manual and industrial training in general mean the training of head, eye and hand in order that the individual may work quickly and intelligently with the least loss of energy and at the same time understand and enjoy his work. The purpose of industrial training is to fit the individual so that he will he more skillful in his work and at the same time a useful, stronger and more intelligent member of society. Industrial training developes the reasoning powers, gives grace and dexterity in movement and is in every way helpful to the individual. The history of industrial training covers only a short period. The first school founded for this purpose was at Bern, Switzerland in 1835. From this small begining they multiplied very fast until by 1860 there were two thousand through out Europe. These schools were established in Europe for economic reasons. It was seen that by giving the common people a thorough industrial education it would help to over come proverty and much of the suffering due to over population. In 1860 industrial traning was introduced into the United States both for its educational value and also for its economic use. Since that time the progress of manual training in both the United States and Europe has been very rapid. Each state of the Union has at least one Chartered College where industrial training is taught. Most of the city schools have manual training of some kind, and many of the private schools and especially the private schools for Negros give attention to industrial training.
Citation: Poston, Adeline. Domestic science in negro schools. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Domestic Science; Domestic Science for African-Americans; African-American History; Enhancing Work Performance; Theses